Occurrence of emerging contaminants in Jakarta Bay, Indonesia: pharmaceuticals and personal care products. Issue 1 (1st January 2023) - Sudaryanto, A; Witama, R O; Nosaki, K; Tanoue, R; Suciati, F; Sachoemar, S I; Hayami, Y; Morimoto, A; Nomiyama, K; Kunisue, T
Abstract: Contamination by emerging contaminants of pharmaceutical and personal care products (PPCPs) has been a matter of global concern due to increasing their occurrence in the environment and their potential toxic effect. Despite the increasing number of publications on PPCPs in aquatic environments worldwide, only very few data are available in Indonesia. This study aims to determine PPCPs in the surface water of Jakarta Bay to understand their occurrence and distribution. Surface water was collected from 17 stations in September 2018. Samples were analyzed for 74 compounds of PPCPs using Ultra-fast Liquid Chromatography coupled with mass spectrometry. In general, among PPCPs analyzed, 20 compounds occur in seawater from Jakarta Bay, of which 15 PPCPs were detected in 50% of the sampling stations. Among PPCPs detected, N, N-diethyl-3-toluamide (DEET), Ibuprofen, O-desmethyl tramadol, Mefenamic acid, Sulfamethoxazole and Tramadol were the predominant with mean and range concentrations of 51(nd-170), 6.9(nd-22), 6.5(nd-31), 4.8(nd-13), 2.2(nd-6.1), and 131.9(nd-4.8) ng/l, respectively. Whereas the other PPCPs were one or more orders of magnitude lower. Generally, concentrations of PPCPs were higher in the inner bay than outer bays. Another study from freshwater rivers which flow to Jakarta Bay showed a high concentration of DEET indicating that the environment was an essential source of PPCPs.